A Silicon Complex of 1,4,7,10-Tetraazacyclododecane (Cyclen) with Unusual Coordination Geometry - Uwe Böhme; Marcus Herbig; Betty Günther (Crystals, 2025)
[1,4,7,10-Tetraazacyclododecano-κ4N1,4,7,10(3-)]silicon(IV) chloride was synthesized from 1,4,7,10-tetraazacyclododecane (cyclen), n-butyl lithium, and silicon tetrachloride. The crystal structure analysis reveals that this cationic compound is a dimer in the solid state with pentacoordinate silicon atoms. The compound was characterized by melting point, IR, and NMR spectroscopy. The quantum chemical analysis shows that this compound might be an interesting precursor to generate a mononuclear silicon (IV) complex with unusual reactivity due to nearly planar tetracoordinate coordination geometry at the silicon atom.